2016
DOI: 10.1007/s00441-016-2437-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies

Abstract: In this study, we extensively screened the in vitro and in vivo effects of PDLSCs following short-term inflammatory and/or hypoxic pretreatments. We found that the 24-h hypoxic pretreatment of PDLSCs significantly enhanced cell migration and improved cell surface CXCR4 expression. In addition, hypoxia-pretreated PDLSCs exhibited improved cell colony formation and proliferation. Cells that were dually stimulated also formed more colonies compared to untreated cells but their proliferation did not increase. Impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 74 publications
(130 reference statements)
1
33
0
1
Order By: Relevance
“…PDLSCs cultured for 24 hours in the IL‐1β (5 ng/mL)/TNFα (10 ng/mL) inflammatory micro‐environment upregulated their expression of CXCR4, to attach to distant SDF‐1/CXCL12, while downregulated it in their resident tissues (see above), thereby increasing their cell migration/homing ability. However, no notable increase in their CFUs ability was observed . Again, it appeared that the two stages of proliferation and homing could not be activated at the same time in the periodontal stem/progenitor cells and need to be timely synchronized.…”
Section: Effect Of Inflammatory Micro‐environment On Periodontal Mscsmentioning
confidence: 92%
See 1 more Smart Citation
“…PDLSCs cultured for 24 hours in the IL‐1β (5 ng/mL)/TNFα (10 ng/mL) inflammatory micro‐environment upregulated their expression of CXCR4, to attach to distant SDF‐1/CXCL12, while downregulated it in their resident tissues (see above), thereby increasing their cell migration/homing ability. However, no notable increase in their CFUs ability was observed . Again, it appeared that the two stages of proliferation and homing could not be activated at the same time in the periodontal stem/progenitor cells and need to be timely synchronized.…”
Section: Effect Of Inflammatory Micro‐environment On Periodontal Mscsmentioning
confidence: 92%
“…Periodontal ligament stem/progenitor cells cultured for 24 hours in IL‐1β (5 ng/mL)/TNFα (10 ng/mL) inflammatory micro‐environment slightly downregulated their expression of RUNX2, ALP, and OC. This effect was even more pronounced, when the inflammatory micro‐environment was combined with a hypoxic state . PDLSCs cultured in osteogenic medium supplemented by monocyte‐derived TNFα exhibited a reduced osteogenic potential.…”
Section: Effect Of Inflammatory Micro‐environment On Periodontal Mscsmentioning
confidence: 98%
“…To detect the expression levels of osteogenic (RUNX‐2, ALP and OCN) and adipogenic (PPAR‐γ) genes and proteins, total RNA and protein were collected at day 7 and then subjected to analysis via real‐time PCR and Western blotting, respectively. The sequences of the primers used for real‐time PCR analysis were described previously . Furthermore, the osteogenic differentiation of the cells in each group was assessed through Alizarin Red staining, while the adipogenic potential was analysed using Oil Red O staining.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of different pretreatments on the expression of osteo- previously. 18 Furthermore, the osteogenic differentiation of the cells in each group was assessed through Alizarin Red staining, while the adipogenic potential was analysed using Oil Red O staining. In parallel, the cells in all groups were incubated with osteogenic medium and adipogenic medium.…”
Section: Cell Differentiation Analysismentioning
confidence: 99%
“…Additionally, short‐term stimulation of BMMSCs with combinations of various cytokines demonstrated up‐regulated cell surface and intracellular CXCR4 expression, leading to improved cell trafficking potential in vitro and in vivo . Although numerous investigations have revealed that either a hypoxic or an inflammatory stimulus may increase the capacity for cell migration, dual stimuli combined with hypoxia and inflammation do not necessarily lead to a synergistic effect . Further strategies to increase and control cell migration in vivo and to control this process may bring us closer to reaching the original goals of stem cell therapy.…”
Section: Increasing the Surface Sensitivity Of Stem Cells To Homing Fmentioning
confidence: 99%